2014
DOI: 10.1146/annurev-pharmtox-011112-140338
|View full text |Cite
|
Sign up to set email alerts
|

Turning Off AKT: PHLPP as a Drug Target

Abstract: Precise control of the balance between protein phosphorylation, catalyzed by protein kinases, and protein dephosphorylation, catalyzed by protein phosphatases, is essential for cellular homeostasis. Deregulation of this balance leads to pathophysiological states, driving diseases such as cancer, heart disease, and diabetes, among many others. Aberrant phosphorylation of components of the pathways that control cell growth cell survival are particularly prevalent in cancer. One of the most studied tumor suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 121 publications
2
102
0
Order By: Relevance
“…There is evidence that the PI3K/Akt signaling pathway is involved in the development of VILI [26] and Akt is also a target of PHLPP2 [27]. In the present study, we further detected the protein expression of PI3k and Akt in HUVECs after MS. Our results show that MS significantly inhibited the activation of the PI3K/Akt signaling pathway (reduced expression of p-PI3K and p-Akt, vs blank and NC groups) and silencing of miR-135a further decreased the expression of p-PI3K and p-Akt (P < 0.05, si-miR-135a+MS vs NC+MS group) (Fig.…”
Section: Expression Of Pi3k P-pi3k Akt and P-aktmentioning
confidence: 52%
“…There is evidence that the PI3K/Akt signaling pathway is involved in the development of VILI [26] and Akt is also a target of PHLPP2 [27]. In the present study, we further detected the protein expression of PI3k and Akt in HUVECs after MS. Our results show that MS significantly inhibited the activation of the PI3K/Akt signaling pathway (reduced expression of p-PI3K and p-Akt, vs blank and NC groups) and silencing of miR-135a further decreased the expression of p-PI3K and p-Akt (P < 0.05, si-miR-135a+MS vs NC+MS group) (Fig.…”
Section: Expression Of Pi3k P-pi3k Akt and P-aktmentioning
confidence: 52%
“…Studies from a number of labs have now implicated loss of PHLPP1 activity as an important facet of cancer cell survival. 23,[36][37][38] That being said, despite the fact that PHLPP1 has a predicted Ras-associated domain, 39 our study is the first (to our knowledge) to directly link downregulation of PHLPP1 to oncogenic Ras signaling. In addition, the majority of studies aimed at understanding PHLPP1 in cancer cells have focused on PHLPP1's ability to dephosphorylate Akt.…”
Section: Discussionmentioning
confidence: 77%
“…The phosphatase PHLPP1 is known to negatively regulate Akt by dephosphorylating the hydrophobic motif (S473). 23,24 To examine if PHLPP1 is negatively regulated by Ras, we assessed PHLPP1 levels in the presence and absence of oncogenic Ras. Indeed, the expression of oncogenic Ras is sufficient to lower the quantities of PHLPP1 in MCF-10A cells (Figure 5c).…”
Section: Resultsmentioning
confidence: 99%
“…We selected to characterize the UBS from the cellular pleckstrin homology domain and leucine-rich repeat protein phosphatase 1 (PHLPP1), because this protein was found to interact with UAF1 in previous proteomic studies (including our own [13]) (data not shown) and to be a substrate of either USP1, USP12, or USP46, depending on the report (17)(18)(19)(20)(21). PHLPP1, and its close homologue PHLPP2, have been shown to regulate the proliferation and survival of normal and cancer cells through their ability to dephosphorylate a common set of substrates, which include the kinases Akt and PKC (22,23). Thus, PHLPP1 and PHLPP2 are not functionally linked to HPV DNA replication in any way, and their only resemblance to E1 is in their ability to bind UAF1 and associated USPs.…”
mentioning
confidence: 89%